2021
DOI: 10.35794/jmbi.v7i3.31526
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perceived Value, Brand Image Terhadap Customer Loyalty Melalui Customer Engagement Sebagai Variabel Mediasi (Studi Pada Pelangan Indihome Pt. Telkom Manado)

Abstract: The study aims to analyze the effect of Perceived Value and Brand Image on Customer Loyalty with Customer Engagement as a Mediation Variable for Indihome Customers at PT. Telkom Manado. The population of this research were Indihome customers in Manado. Sampling was carried out based on Isaac Michael's table of 267 respondents. The research data were analyzed using PLS SEM (Partial Least Square - Structural Equation Modeling) with SmartPLS 3.0 software. The results showed that Perceived Value and Brand Image ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 3 publications
1
7
0
6
Order By: Relevance
“…29 dengan calan pelanggan dan pelanggan saat ini. Customer Relationship Manajemen adalah strategi tingkat korporasi yang berfokus pada pembangunan dan pemeliharaan hubungan dengan pelanggan, jadi CRM lebih menekankan pada pendekatan holistic terhadap falsafah organisasi yang menekankan hubungan yang erat dengan pelanggan [9].…”
Section: Crm (Customer Relationship Manajement)unclassified
“…29 dengan calan pelanggan dan pelanggan saat ini. Customer Relationship Manajemen adalah strategi tingkat korporasi yang berfokus pada pembangunan dan pemeliharaan hubungan dengan pelanggan, jadi CRM lebih menekankan pada pendekatan holistic terhadap falsafah organisasi yang menekankan hubungan yang erat dengan pelanggan [9].…”
Section: Crm (Customer Relationship Manajement)unclassified
“…Despite the fact that previous research has demonstrated that highly religious adherents behave differently and have their own criteria in purchasing decisions (Amir, 2021), Al Nawas et al (2021) noted that there is a lack of research in consumer research that can prove the effect of religiosity in changing consumer patronage behaviour specifically in the context of Muslim consumers. Moreover, empirical study on these concepts in consumer behaviour has been scarce, and its significance in the field is still not widely recognised.…”
Section: Problem Statementmentioning
confidence: 99%
“…However, the Islamic worldview and the centrality of ethics in that worldview are necessary conditions for the existence of such principles and standards. Faith in and loyalty to Allah SWT, the giver of all good things and final arbiter of right and wrong, is central to this worldview (Amir, 2021). Understanding the elements that influence consumers' online shopping behavior is crucial for both researchers and online retailers.…”
Section: Literature Review Online Purchase Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…‫البحثية:‬ ‫الفجوة‬ :ً ‫ثالثا‬ ‫الدراسات‬ ‫ما‬ ‫العديد‬ ‫قامت‬ (Xu et al, 2020; Islam and Rahman, 2016;) ‫بدراسة‬ ‫العميل.‬ ‫ارتباط‬ ‫على‬ ‫ا‬ ‫وتأثير‬ ‫المقصد)‬ ‫عالمة‬ ‫وجودة‬ ‫العالمة‬ ‫(صورة‬ ‫منل‬ ‫العالمة‬ ‫إنصاف‬ ‫أبعاد‬ ‫بع‬ ‫دراسة‬ ‫تناولت‬ ‫حيا‬ ‫في‬ (Zhang et al, 2015) ‫إنصاف‬ ‫دور‬ ‫كمقدمات‬ ‫البعد‬ ‫أحادي‬ ‫كمتغير‬ ‫العالمة‬ ‫الدراسات‬ ‫ما‬ ‫عدد‬ ‫تناولت‬ ‫حيا‬ ‫في‬ ‫العميل.‬ ‫ارتباط‬ ‫الي‬ ‫تؤدي‬ ‫التي‬ ‫الدوافع‬ ‫وأحد‬(Greve, 2014;Prentice et al, 2019;Huerta-Álvarez et al, 2020;Amir et al, 2021) …”
unclassified